The Influence of Organizational Culture, Rewards, and Work Environment on Employee Performance at Al Falah Bakery - Abdur Rahman; Muchson, M. (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research Objectives: This study aims to investigate the interaction between organizational culture, reward system, and work environment in shaping employee performance at Al Falah Bakery. Specifically, this study will: (1) analyze how organizational culture affects employee performance; (2) assess the impact of the existing reward system on employee performance; (3) identify the influence of work environment on employee performance; and (4) explore the combined effects of these three variables on employee performance. By examining these reciprocal relationships, this study seeks to provide valuable insights for Al Falah Bakery to optimize its organizational practices and improve employee performance. Design/ Method/Approach: This quantitative research is based on the philosophy of positivism, utilizing primary data collected through questionnaires and analyzed using SPSS software version 25. This study focuses on a population consisting of all employees, with a sample size of 30 participants. This approach emphasizes objective measurement and statistical analysis to draw conclusions about the phenomenon being studied. However, the limited sample size may limit the generalizability of the findings, so further research is needed          a larger and more representative sample to confirm and expand the conclusions drawn from this study. Results findings: The study revealed that organizational culture, rewards, and work environment are important factors that contribute to employee performance. A strong and positive organizational culture fosters a sense of belonging and purpose, encouraging employees to perform at their best. Similarly, a well designed reward system that recognizes     and     rewards     employee     contributions    motivates individuals to excel. Furthermore, a conducive work environment that enhances well being and facilitates productivity enhances employee performance. These findings underscore the importance of a holistic approach to human resource management that prioritizes creating a supportive and rewarding workplace to maximize employee potential and achieve organizational goals .